Replication of Migraine GWAS Susceptibility Loci in Chinese Han Population. Issue 4 (25th March 2014) - Fan, Xiaoping; Wang, Jing; Fan, Wen; Chen, Lixue; Gui, Bei; Tan, Ge; Zhou, Jiying
<x xml:space="preserve">Abstract</x> Background Recent genome‐wide association studies (GWAS) have identified 3 genetic variants that are strongly associated with migraine in Europeans. The effect of these risk variants in other populations is unknown. To further replicate the GWAS findings, we investigated the 3 variants rs2651899 (1p36.32, PRDM16), rs10166942 (2q37.1, TRPM8), and rs11172113 (12q13.3, LRP1) for their association with migraine in the Chinese Han population. Methods We performed a case–control association study. Genomic DNA was collected from 608 unrelated individuals, including 304 migraineurs (41 migraine with aura and 263 migraine without aura) and 304 healthy controls. Genotyping of single nucleotide polymorphisms (SNPs) was performed by ligase detection reaction method. Results We identified the minor allele of rs2651899 located in PRDM16 to be associated with migraine (P = .005, odds ratio = 1.382, 95% confidence interval = 1.100‐1.736), the association remain significant after Bonferroni correction. For the other 2 SNPs (rs10166942 and rs11172113), no statistically significant differences were observed in the allele/genotype frequencies between cases and controls. None of the 3 SNP was associated with specific migraine features. Conclusion Our study confirmed the association of PRDM16 to migraine susceptibility in the Chinese Han population. The results also indicated that replication studies of previous GWAS findings across populations is of importance to validate these associations and to gain a better understanding of migraine susceptibility of potential genetic heterogeneity between populations. Further work is necessary to understand the functional mechanisms underlying these variants identified by GWAS.